2014
DOI: 10.1021/pr4008333
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomic and Transcriptomic Analyses of Molecular Mechanisms Associated with Low Silk Production in Silkworm Bombyx mori

Abstract: To investigate the molecular mechanisms underlying the low fibroin production of the ZB silkworm strain, we used both SDS-PAGE-based and gel-free-based proteomic techniques and transcriptomic sequencing technique. Combining the data from two different proteomic techniques was preferable in the characterization of the differences between the ZB silkworm strain and the original Lan10 silkworm strain. The correlation analysis showed that the individual protein and transcript were not corresponded well, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 73 publications
(119 reference statements)
5
66
1
Order By: Relevance
“…Similar results have been reported in several previous studies (Lan et al, 2012; ArcondĂ©guy et al, 2013; Wang et al, 2014). The regulation of mRNA synthesis, the post-transcriptional regulation of mRNA splicing and supervision mechanism, and the post-translational modification of the mRNA translated product can all result in altered protein levels (ArcondĂ©guy et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results have been reported in several previous studies (Lan et al, 2012; ArcondĂ©guy et al, 2013; Wang et al, 2014). The regulation of mRNA synthesis, the post-transcriptional regulation of mRNA splicing and supervision mechanism, and the post-translational modification of the mRNA translated product can all result in altered protein levels (ArcondĂ©guy et al, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Majeran et al (2005) reported that among the 125 chloroplast proteins quantified in the three methods (2-DE, ICAT, and label-free), only 20 proteins were quantified in common. Moreover, the SDS-PAGE-based and gel-free-based proteomic techniques were combined to explore the molecular mechanism responsible for low silk production, a total of 17 of 174 changed proteins were common between the two techniques (Wang et al, 2014). Similarly, here, we identified 85 changed proteins using gel-based and gel-free techniques, among which only 12 proteins were commonly identified by two methods.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that silkworm PSGs that express Bcl-2-associated X protein become ablated (17), although this study did not present information on the cocoons and the development of the manipulated individual after pupation. Furthermore, a separate report describing T7 RNA polymerase-modified PSGs of transgenic silkworms showed decreased but detectable FibL and FibH expression (33), whereas another study showed that silkworms with transcription activatorlike effector nuclease-mediated FibH gene disruption produced thin-layered cocoons containing no FibH but a normal level of FibL (34). The Nd silkworm strain has a natural genetic mutation that affects silk glands and produces small quantities of cocoons that have very high amounts of sericin and varying percentages of fibroin (22).…”
Section: Discussionmentioning
confidence: 98%
“…19 Significant enhancements were observed in this strain for proteasome pathway, glycolysis/gluconeogenesis, and TCA cycle, indicating the enhanced protein degradation and energy metabolism. 19 …”
Section: Introductionmentioning
confidence: 83%